Dietary Supplements and Human Health - Chiba, Tsuyoshi (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The prevalence of dietary supplement is increased in the world. The primary purpose of dietary supplements is the provide nutrients, such as vitamin and mineral, to maintain health. However, the functional ingredients in food, especially polyphenols, have attracted attention in recent decades, and these ingredients have beneficial effects on human health. On the other hand, a lot of ingredients with poor evidence as to their effects have also been marketed as dietary supplements, and adverse events associated with dietary supplement use have been reported. It is important to choose dietary supplements whose efficacy and safety for our health have been studied.